Functional trajectories before and after a new cancer diagnosis among community-dwelling older adults - Presley, C.J. (J Geriatr Oncol, 2018)
BACKGROUND: To characterize functional trajectories in the year before and after a new cancer diagnosis among older adults and to identify risk factors for worsening disability post-diagnosis. METHODS: We identified 170 participants 70+ years with monthly assessments of thirteen basic, instrumental, and mobility activities and with a new cancer diagnosis from 1998 to 2014. A group-based trajectory model identified distinct functional trajectories based on a total disability score during the twelve months pre- and post-diagnosis. We evaluated associations between potential risk factors at the time of cancer diagnosis and worsening disability post-diagnosis, explored functional transitions from pre- to post-diagnosis and identified participants whose functional trajectories worsened. RESULTS: Three pre-diagnosis functional trajectories were identified among 170 participants (mean age at diagnosis: 83 years (range: 73–105 years): mild, moderate, and severe disability. Three post-diagnosis functional trajectories were identified among 158 non-decedents: mild, moderate, and severe disability. Most participants (93.9%) with severe disability pre-diagnosis had severe disability post-diagnosis. Risk factors independently associated with worsening disability post-diagnosis included moderate or severe disability pre-diagnosis (adjusted risk ratio, aRR: moderate: 2.96; 95%CI: 2.11–4.16; severe: 5.11; 95%CI: 3.07–8.52) vs. mild (reference), poor physical capability (aRR: 1.57; 95%CI: 1.07–2.30), and incurable stage (aRR:1.99; 95%CI: 1.41–2.80). 40% of participants with a mild or moderate disability trajectory pre-diagnosis transitioned to a worse functional trajectory post-diagnosis. CONCLUSION: Older adults followed distinct functional trajectories in the twelve months before and after cancer diagnosis. Functional trajectory pre-diagnosis, poor physical capability, and incurable stage were independent risk factors for worsening disability post-diagnosis.